Advances in Fractional Lyapunov-Type Inequalities: A Comprehensive Review - Sotiris K. Ntouyas; Bashir Ahmad; Jessada Tariboon (Foundations)
In this survey, we have included the recent results on Lyapunov-type inequalities for differential equations of fractional order associated with Dirichlet, nonlocal, multi-point, anti-periodic, and discrete boundary conditions. Our results involve a variety of fractional derivatives such as Riemann–Liouville, Caputo, Hilfer–Hadamard, <semantics>ψ</semantics>-Riemann–Liouville, Atangana–Baleanu, tempered, half-linear, and discrete fractional derivatives.